2018
DOI: 10.18357/ijcyfs93201818276
|View full text |Cite
|
Sign up to set email alerts
|

Viewing Habits and Identification With Television Characters Among at-Risk and Normative Children and Adolescents

Abstract: This study examined the relationship between participants’ negative or positive identification with television characters and their behavior, and how their reactions in times of anger — whether simply negative or physically violent — varied between at-risk participants and normative ones. Participants were 86 children and adolescents from Israel who filled in four questionnaires on the topics of viewing habits, attitudes, self-image, and aggression. The findings revealed that at-risk children and adolescents r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…However, of all the content, adolescents mostly watch movies and series. The results are consistent with other research, which showed that boys are more inclined to follow sports content, and girls to entertaining, as well as that adolescents watch movies and series the most, and the least media content in the field of art and documentary program (Zilka, 2018). These results meet the predicted expectations that adolescents watch television passively and that their entertainment content is more attractive than others.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, of all the content, adolescents mostly watch movies and series. The results are consistent with other research, which showed that boys are more inclined to follow sports content, and girls to entertaining, as well as that adolescents watch movies and series the most, and the least media content in the field of art and documentary program (Zilka, 2018). These results meet the predicted expectations that adolescents watch television passively and that their entertainment content is more attractive than others.…”
Section: Discussionsupporting
confidence: 91%
“…Such topics, in addition to being less represented, are also less attractive for students to read. In a recent study of adolescents, their low propensity to read such topics has been confirmed (Zilka, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the immediate behavioral effects of identification with TV characters, watching programs involves psychological processes that affect the consolidation of identity in the long term, not only immediately. Researchers (Bandura, 1971(Bandura, , 1986(Bandura, , 2001Cole & Leeds, 1999;Hough & Erwin, 2010;Livingston & Das, 2010;Morgan & Shanahan, 2010;Rideout et al, 2010;Vandewater et al, 2006;Wilson, 2011;Zilka, 2014;Zilka & Romi, 2018) have claimed that television presents a wide range of role models and offers children and adolescents an opportunity to try out and compare alternate identities. In this way, television offers a rich variety of characters to children as role models, and exposes them to characters to which they are unlikely to have been exposed face-to-face in real life.…”
Section: The Media: a Part Of The Children And Youth Environmentmentioning
confidence: 99%
“…Several studies have examined user attitude and media consumption (Roberts, 2000;Mayhew & Weigle, 2018;Mayhew & Weigle, 2018). Other academics have concentrated on one type of media, such as television (Tahira Shah & Khurshid, 2017;Cohen, Zilka & Romi, 2018;Abd Halim & Rosidi, 2012), music (Celasin, 2013;Bryson, 1996), or social media (Rutledge et al, 2019;Adegboyega, 2020;Avunduk et al, 2020;Adegboyegan, 2020;Khammatova et al, 2021). Pre-service teachers' media content choices have not been studied nationally.…”
Section:  Introductionmentioning
confidence: 99%